Framing sustainable development through descriptive determinants in private hospitals – Orientation and organization. (August 2019) - Rodriguez, Rocio; Svensson, Göran; Otero-Neira, Carmen
Highlights: Report the main determinants of orientation and organization from hospitals' past and present sustainability. Reveals descriptive determinants of sustainable development in private hospitals. Divides these determinants into two categories, namely the orientation and organization. Sustainability orientation has changed from value-based initiatives to business-based ones. The orientation changing from environmental initiatives to social ones. Abstract: Purpose: To frame the sustainable development in private hospitals, based on descriptive determinants of orientation and organization from the past to the present. Design/methodology/approach: Based on an inductive approach, judgmental sampling was used to target relevant health care organizations. Informants were assessed according to their knowledge of their organizations' sustainability initiatives. Findings: Report the main determinants of orientation and organization revealed in relation to the hospitals' past and present sustainability initiatives, providing a foundation for describing their sustainable development. Research limitations/implications: Reveals a selection of descriptive determinants of sustainable development in private hospitals, all of which offers a basis for assessing whether the evolution of organizational sustainability initiatives is major, minor or non-existent. Managerial implications: The sustainability orientation has changed from value-based initiatives to business-based ones. It has also resulted in the orientation changing from environmental initiatives to social ones, as well as a change from reactive initiatives to proactive ones. Originality/value: Contributes to framing sustainable development through descriptive determinants in private healthcare organizations. It also divides these determinants into two categories, namely the orientation and organization of sustainability initiatives.